Health and environment, prevention or precaution? - Bard, Denis (Soins; la revue de référence infirmière, 2018)
The health status of the populations of developed countries has never been as satisfactory, but will it stay that way? Research on the subject is difficult due to the complex interactions between our environment and our health, with risks inherent to each noxious agent. Preventing the risks proven to be linked to the quality of our living environments is usually the responsibility of authorities, but individuals can also adopt precautionary practices.